Young woman with mild bone marrow dysplasia, GATA2 and ASXL1 mutation treated with allogeneic hematopoietic stem cell transplantation. Issue 2 (2015) - Lübking, Anna; Vosberg, Sebastian; Konstandin, Nikola P.; Dufour, Annika; Graf, Alexander; Krebs, Stefan; Blum, Helmut; Weber, Axel; Lenhoff, Stig; Ehinger, Mats; Spiekermann, Karsten; Greif, Philipp A.; et al.
Abstract: Heterozygous mutations in GATA2 underlie different syndromes, previously described as monocytopenia and mycobacterial avium complex infection (MonoMAC); dendritic cell, monocytes, B- and NK lymphocytes deficiency (DCML); lymphedema, deafness and myelodysplasia (Emberger syndrome) and familiar myelodysplastic syndrome/acute myeloid leukemia (MDS / AML). Onset and severity of clinical symptoms vary and preceding cytopenias are not always present. We describe a case of symptomatic DCML deficiency and rather discrete bone marrow findings due to GATA2 mutation. Exome sequencing revealed a somatic ASXL1 mutation and the patient underwent allogeneic stem cell transplantation successfully. Highlights: Allogeneic stem cell transplantation was performed for DCML caused by GATA2 mutation. Genetic diagnostics were done by Sanger sequencing and whole exome sequencing. We identified an ASXL1 mutation associated with high risk for leukemic transformation.